Diagnosis of Bank Financing of Mexican MSMEs: Progress and Challenges - Jiménez Rico, Artemio; Galván Zavala, Karina; Gutiérrez Rangel, Héctor Fabián (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: Carry out a diagnosis of bank financing to contribute find solutions to the problem of access to financing. MATERIAL AND METHOD: It is of a qualitative type with an exploratory scope and a non-experimental and cross-sectional research design. The technique was the collection of secondary data from ENAFIN 2018 and ENAPROCE 2018. RESULTS: It was found that microenterprises are the ones that face the greatest restrictions in access to bank financing, for example: in 2018 only 14.6% had financing; 47.3% indicated that the lack of credit history was the main reason why they were not granted financing. In the heat maps, it stands out that the state of Coahuila is where SMEs have the least access to credit from commercial banks with only 8.7%, while Campeche, Guerrero, and Puebla are the states with the highest financing with 71.5%, 67.9%, and 60.6%, respectively. CONCLUSIONS: There is a large gap in access to bank financing between MSMEs and large companies, and high-interest rates are the main restriction of access to credit.